Developing a fuel cell/battery converter for electric vehicles - Aung, Si Hein (2016)
Energy is one of the most valuable commodities in today’s world. It is needed everywhere and the demand is too big till the limited non-renewable resources like fossil fuels are going to deplete in the near future. Despite being a major source of energy in the world today, fossil fuels are aslo not environment-friendly or eco-friendly. Therefore, there is a need to investigate other sources of energy with little or no environmental impact. Fuel cell energy is one those alternative clean energies.